2017
DOI: 10.1016/j.vaccine.2017.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of childhood seasonal influenza vaccination in Singapore: A cross-sectional survey

Abstract: Knowledge and willingness to vaccinate was high in this parent population, but influenza vaccine uptake in children was low. Encouraging medical professionals to recommend vaccination of eligible children is key to improving uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 37 publications
4
41
0
2
Order By: Relevance
“…Some confused Avian flu with seasonal flu while others magnified side effects of the vaccine. Concerns over the vaccine's efficacy, perceived lack of vulnerability, fear of side effects, and a perception that vaccines are not necessary were common barriers to vaccination that were also reflected in our data from older adults [5,14]. The important role of advice from healthcare workers to improve vaccine uptake is consistent with work looking at diabetic patients and parents of pre-school children [13,14].…”
Section: Comparing With Other Studiessupporting
confidence: 66%
See 1 more Smart Citation
“…Some confused Avian flu with seasonal flu while others magnified side effects of the vaccine. Concerns over the vaccine's efficacy, perceived lack of vulnerability, fear of side effects, and a perception that vaccines are not necessary were common barriers to vaccination that were also reflected in our data from older adults [5,14]. The important role of advice from healthcare workers to improve vaccine uptake is consistent with work looking at diabetic patients and parents of pre-school children [13,14].…”
Section: Comparing With Other Studiessupporting
confidence: 66%
“…This study identified novel and previously unrecognized issues as well as confirm previous observations. Comparing with other local studies on attitudes and knowledge of influenza vaccines, it is evident that poor understanding and misconceptions are also prevalent in other target groups, such as people with diabetes and healthcare workers [5,14]. Some confused Avian flu with seasonal flu while others magnified side effects of the vaccine.…”
Section: Comparing With Other Studiesmentioning
confidence: 94%
“…Parental awareness of IMD is crucial as it may influence the decision to vaccinate children [44,45]. However, only 72.5% of parents in the present study had ever received information about IMD.…”
Section: Discussionmentioning
confidence: 80%
“…Of the 10 of 57 studies that found an association between belief in the efficacy of the vaccine and vaccination status, 2 investigated all childhood vaccines (24,84), and 7 investigated attitudes and beliefs about influenza vaccine (39,47,64,73,77,80). In 11 of the 57 studies, an association was found between vaccination status and trust in doctors and health care professionals or recommendations from a doctor (24,41,66,69,80,(85)(86)(87)(88)(89). Of those, 6 participants were asked about all childhood vaccines (24,68,69,(85)(86)(87), and influenza vaccines in 4 studies (41,66,80,88).…”
Section: Associations Between Attitudes and Beliefs With Vaccination mentioning
confidence: 99%
“…In 11 of the 57 studies, an association was found between vaccination status and trust in doctors and health care professionals or recommendations from a doctor (24,41,66,69,80,(85)(86)(87)(88)(89). Of those, 6 participants were asked about all childhood vaccines (24,68,69,(85)(86)(87), and influenza vaccines in 4 studies (41,66,80,88).…”
Section: Associations Between Attitudes and Beliefs With Vaccination mentioning
confidence: 99%